Land Acquisition And Payment: Some Ground Realities In Uttar Pradesh. - Fahimuddin (2011)
Presently the issue of land acquisition and compensation payment has assumed a very serious dimension in the State of Uttar Pradesh. The farmers are agitating violently against their land acquisitions of present and past, which they perceive, has been at much lower rates than the market value of their land. The paper seeks to analyze, on the basis of primary data, the quantum of land lost by the farmers and the amount of compensation paid to them in industrial and housing projects in Ghaziabad and Lucknow districts of the UP. The various problems encountered by the farmers in getting compensation and utilization of compensation money have also been studied. In the light of various problems faced by the farmers and their demand of higher compensation, the Land Acquisition Act, 1864 and the Rehabilitation and Resettlement Policy of the Government of Uttar Pradesh, pronounced on April 30, 2010 have been examined to find out to what extent the new policy of the state would resolve the contentious issue of land acquisition and compensation payment. The findings in the paper indicated that farmers have been losers in the past from all angles and despite their protests and agitations; the state is showing a cold response to their genuine demands. On the basis of analysis in the paper, a comprehensive strategy has been suggested which can be helpful in solving; one of the most challenging tasks; the state government of Uttar Pradesh is facing at present.